2021
DOI: 10.1186/s13213-021-01641-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bacillus in fermented soybean foods on human health

Abstract: Purpose Fermented soybean foods (FSF) is popularly consumed in the South-East Asian countries. Bacillus species, a predominant microorganism present in these foods, have demonstrated beneficial and deleterious impacts on human health. These microorganisms produce bioactive compounds during fermentation that have beneficial impacts in improving human health. However, the health risks associated with FSF, food pathogens, biogenic amines (BAs) production, and late-onset anaphylaxis, remain a conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 101 publications
0
21
0
Order By: Relevance
“…Bacillus biofilm formation supports the host organism against the gastrointestinal tract (GIT), urogenital tract (UGT), and urinary tract (UT) infections, while modulating immune system activity [ 2 ]. Our further analyses revealed that B. amyloliquefaciens also form biofilms ( Supplementary Figure S4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacillus biofilm formation supports the host organism against the gastrointestinal tract (GIT), urogenital tract (UGT), and urinary tract (UT) infections, while modulating immune system activity [ 2 ]. Our further analyses revealed that B. amyloliquefaciens also form biofilms ( Supplementary Figure S4 ).…”
Section: Discussionmentioning
confidence: 99%
“…A considerable group of bacterial probiotics is based on the Bacillus genus, with commonly mentioned B. subtilis , B. coagulans , B. pumilus , B. licheniformis , and B. clausii [ 1 ]. These species are a field of rising scientific interest and they offer a potential for industrial applications, being commonly found in the Asian and West African Bacillus fermented foods (BFFs), based on soybeans and locust beans [ 2 ]. Bacillus species are also promising and particularly important for an fast growing group of lactose-intolerant individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Intra/inter-species diversity of Bacillus, both culturable and unculturable, in kinema exists and co-exists for the survival and competition among different species. The dominance of Bacillus in fermented soybean foods is probably due to the alkalinity of the product during fermentation (Gopikrishna et al, 2021) and also its proteolytic activity (Nguyen and Nguyen, 2020). Predominant Bacillus with different species has been reported in other Asian fermented soybean foods such as cheonggukjang (Nam et al, 2012;Tamang et al, 2022), natto (Kubo et al, 2011), pe poke (Tamang et al, 2021b), douchi (Hu et al, 2019), and thua nao (Pakwan et al, 2020).…”
Section: Microbial Structurementioning
confidence: 99%
“…This strain has strong acid and heat tolerance, can successfully reach the intestinal tract, regulate gut microbiota disorders and has many biological functions, such as reducing blood lipids, thrombolytic and anti‐inflammation (Peng et al, 2012). It is reported that the extract from peanut meal fermented with Bacillus natto can protect intestinal barrier, improve epithelial function and promote intestinal health in hyperlipidaemic mice (Gopikrishna et al, 2021).…”
Section: Introductionmentioning
confidence: 99%